Are we ready for a gender-specific approach in interventional cardiology?. (1st July 2019) - Calabrò, Paolo; Niccoli, Giampaolo; Gragnano, Felice; Grove, Erik Lerkevang; Vergallo, Rocco; Mikhailidis, Dimitri P.; Patti, Giuseppe; Spaccarotella, Carmen; Katsiki, Niki; Masiero, Giulia; Ueshima, Daisuke; Pinar, Eduardo; et al.
Abstract: Gender differences in the pathophysiology of atherosclerosis, cardiovascular risk factors, and diagnosis of coronary artery disease and valvular heart disease are well known. Such differences have also been outlined in the management and outcomes after acute coronary syndromes and valvular repair. Regarding the atherosclerotic process, pathological experimental studies suggest that plaque composition and burden may differ by gender. Female gender is associated with worse outcomes in the case of ischemic heart disease and, compared with men, women are less likely to undergo interventional cardiac procedures and sustain worse outcomes. In the setting of valvular heart disease (VHD), transcatheter aortic valve implantation (TAVI) and percutaneous edge-to-edge mitral valve repair are now well-established procedures with high success rates. In women with moderate to severe aortic stenosis, subgroup analyses in TAVI trials have demonstrated gender-related differences suggesting female gender as beneficial in terms of short-, mid-, and long-term outcomes. Similarly, several studies reported different procedural challenges and outcomes in males and females following surgical and percutaneous mitral valve repair. These diverse findings emphasize the necessity to provide gender-specific analyses of interventional methods. This review highlights gender differences in the epidemiology, pathophysiology, treatment options and clinical outcomes of the conditions mentioned above. Highlights: Gender differences in the pathophysiology and clinical presentation of coronary and valvular heart disease have been shown. In the case of ischemic heart disease, females are less likely to receive timely and evidence-based treatment than males. In female gender, percutaneous valvular interventions have shown similar (or even better) short- and long-term outcomes. Further studies are necessary to investigate and solve open gender-related issues in contemporary interventional cardiology.